Borderlord Scuttle - Cromhout, Luke Jacob (Department of English Language and Literature, 2022)
Borderlord Scuttle is set in an alternate version of South Africa's Eastern Cape based on the fictional papers of a thief named JB Niemand and the story follows his first adventure. After the end of a relationship with an artist named Rebekah, JB Niemand's own artistic aspirations dashed. He is uninspired and directionless with no way to sustain himself, let alone pursue a career as a painter. To solve both problems he turns to a life of crime. With his profits he plans to complete a pilgrimage to Alice to see a Walter Battiss artwork that Rebekah claimed would finally make him the artist he dreamed of becoming. However, he is no master criminal. The story begins when JB Niemand finds himself in prison. At Middledrift Corrections JB Niemand develops a dependent and ambiguous relationship with Stix, a career criminal who will end up abandoning JB in the bush shortly after their escape from prison. Stix's betrayal catalyses JB's becoming and he is propelled into a journey that sees him attempting to join a gang of hill bandits who call themselves the Ninevites, drinking in a small town bar in The Settler Flats, and eventually making good on his plans to go to Alice.